The phylogenetic status of Limnonectes liui (Yang, 1983) (Anura: Dicroglossidae) based on mitochondrial genes and its taxonomic implications - Huang, Jiayue; Li, Zheng; Liu, Xiaolong; Stuart, Bryan L.; Yuan, Zhiyong; Zhao, Haipeng (Zootaxa, 2022)
Limnonectes liui (Yang, 1983) is a poorly known frog from Yunnan Province, China, with a confusing taxonomic history. We use mitochondrial (mt) DNA sequence data from newly collected specimens to reconstruct the phylogenetic position of the species. Limnonectes liui was found to be deeply nested within the geographically widespread dicroglossid frog L. limborgi (Sclater, 1892), verifying its placement within the genus Limnonectes but casting doubt on its distinction as a species. Morphological comparisons of the holotype and newly collected specimens of L. liui to specimens of L. limborgi from across its range also corroborated the hypothesis that these two species are conspecific, and we recommend treating L. liui as a junior synonym of L. limborgi. Our study underscores the importance of making comparisons with species found beyond a country’s border when describing new species.